"…Not Having the Real Support That We Need": Patients' Experiences With Ambiguity of Systemic Lupus Erythematosus and Erosion of Social Support. Issue 3 (22nd April 2019) - Leung, Jerik; Ra, Jennifer; Baker, Elizabeth A.; Kim, Alfred H. J.
Abstract : Objective: The patient‐specific experience of living with systemic lupus erythematosus (SLE) is underreported, particularly when studying factors associated with health‐related quality of life (HRQOL). Recent work has suggested that biomedical interventions are only partially predictive of HRQOL measures. A qualitative analysis of patient‐specific experiences can uncover additional root causes of impaired HRQOL in populations with SLE beyond the scope of quantitative questionnaires. Methods: Consented adult patients with SLE classified by the American College of Rheumatology or Systemic Lupus International Collaborating Clinics were recruited. Ten semistructured interviews were conducted across six participants. Interviews were audio recorded, transcribed, and analyzed using an iterative process. Findings were presented to an interactive public forum with patients with SLE, family members and friends of patients, and health care professionals to assess accuracy. Results: Four themes emerged from the interviews: 1) ambiguity, inconsistency, and lack of symptom predictability due to SLE disease courses; 2) poor communication with family, friends, and/or partners and poor bidirectional communication between health care providers and patients (informational support); 3) lack of validation for patients' experiences (appraisal support); and 4) problematic aspects of social support, including negative support and patients' inability to reciprocate support because of role changes. Data also indicate a reciprocal association between appraisal and informational sources of support. Conclusion: Findings indicate that inadequate appraisal and informational support from informal and formal sources are salient factors influencing HRQOL among patients with SLE. Findings also point to the necessity of integrating community organizations, physicians, and friends and family of patients with SLE into capacity‐building interventions aimed at enhancing these sources of social support.